The supervisor and the school: a never ending relationship? - Soraya Romano Pacífico (Cadernos de Letras da UFF, 2018)
In this paper, we examine, from the theoretical perspective of Pecheux’s Discourse Analysis, the supervisor’s position and his/her relationship with schools. We demonstrate how this subject-position is constituted and interspersed with power relations and discursivities which make him/her responsible for overseeing both the teaching practice and the school environment.